Quail carcass quality with Pseudomonas putida bioemulsifier in effervescent tablet form through drinking water - Maulana, Achmad Firman; Ali, Abdul Hafiizh Nashrulloh; Fahrudin, Abdi Eka Robbich; Hakiki, Muhammad Adam Ridho; Ningsih, Niati; Wulandari, Suci; Pantaya, Dadik (Politeknik Negeri Jember, 2025)
This study aims to determine the effect of adding effervescent bioemulsifier tablets from Pseudomonas putida through drinking water on the quality of broiler quail carcasses. This study used 200 male Golden Quails, divided into 4 treatments and 5 replications, each consisting of 10 quails. The treatments included T0, which was the control drinking water without any bioemulsifier, and T1, T2, and T3, which were supplemented with 0.1, 0.2, and 0.3 g of bioemulsifier/L of drinking water, respectively. The parameters that were observed included the carcass percentage, the physical quality of the carcass, and the amount of abdominal fat in the broiler quail. The experiment was carried out from week 3 to week 5. The experiment used a completely randomised design (CRD), if significantly different, and continued with the Duncan Multiple Range Test (DMRT). The results of this study showed that the addition of bioemulsifier in effervescent form through drinking water in broiler quail was significantly different (P<0.05) on the percentage of carcass and pH value of meat. The conclusion of this study is that the addition of effervescent bioemulsifier tablets to drinking water has an effect on increasing the carcass percentage and pH value of broiler quail.